2019
DOI: 10.1007/978-3-030-10801-4_19
|View full text |Cite
|
Sign up to set email alerts
|

Forbidden Directed Minors, Directed Path-Width and Directed Tree-Width of Tree-Like Digraphs

Abstract: In this paper we consider the directed path-width and directed tree-width of recursively defined digraphs. As an important combinatorial tool, we show how the directed path-width and the directed tree-width can be computed for the disjoint union, order composition, directed union, and series composition of two directed graphs. These results imply the equality of directed path-width and directed tree-width for all digraphs which can be defined by these four operations. This allows us to show a linear-time solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The set of all these digraphs is denoted by extended directed co-graphs, since it generalizes directed co-graphs. In [GR18a] we showed that the result of [GR18b] even holds for extended directed co-graphs. For the class of extended directed co-graphs it remains to show how to compute an ex-di-co-tree and to find forbidden subdigraph characterizations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The set of all these digraphs is denoted by extended directed co-graphs, since it generalizes directed co-graphs. In [GR18a] we showed that the result of [GR18b] even holds for extended directed co-graphs. For the class of extended directed co-graphs it remains to show how to compute an ex-di-co-tree and to find forbidden subdigraph characterizations.…”
Section: Discussionmentioning
confidence: 92%
“…In [JRST01] the directed union was introduced as a generalization of the disjoint union and the order composition. In [GR18a] we considered digraphs which can be defined by disjoint union, order composition, directed union, and series composition of two directed graphs. The set of all these digraphs is denoted by extended directed co-graphs, since it generalizes directed co-graphs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we conclude that directed co-graphs and the considered generalizations lead to subclasses of perfect digraphs [AH15]. For directed cactus forests, which is a set of digraphs of directed tree-width 1 [GR19b], the results of [Wie19] and [MSW19] lead to an upper bound of 2 for the dichromatic number and that an optimal acyclic coloring can be computed in polynomial time. We show that this even can be done in linear time.…”
Section: Introductionmentioning
confidence: 81%
“…We have stated the following Lemma in [15] for directed path-width and directed tree-width. The proof is extendable straight-forward to DAG-width and cycle rank.…”
Section: Directed Graph Parameters On Twin-dh Digraphsmentioning
confidence: 99%